Copyright Infringement of Online OTT: Challenges and Solutions in the Evolving Era of Content Piracy - Shukla, Prakhar (Trinity Law Review, 2023)
The rise of Over-The-Top (OTT) platforms has revolutionized the way entertainment content is consumed worldwide. However, along with the growth of OTT services, there has been a significant increase in copyright infringement issues.The paper begins with an introduction that highlights the impact of technology and the internet on copyright infringement. This paper aims to examine the liabilities on infringement of copyright of OTT content. It will discuss the legal framework for intellectual property rights in the evolving era of OTT, including the relevant provisions of the Copyright Act of 1957 in India. It will also explore the concept of OTT content piracy, including the different forms of infringement, the challenges faced by OTT platforms and production houses, and the impact of piracy on the entertainment industry. The paper will further analyse the potential liabilities for OTT platforms, users, and other stakeholders in case of copyright infringement, including civiland criminal liabilities, damages, and penaltiesThe paper will also discuss the measures that can be taken to mitigate OTT content piracy, including the need for reforms to the copyright laws, stricter enforcement mechanisms, technological solutions, and awareness campaigns. It will highlight the importance of creating a conducive legal environment that protects the rights of content creators, encourages innovation, and promotes legitimate use of copyrighted content in the OTT ecosystemIn conclusion, the paper emphasizes the need for immediate reforms to copyright laws to mitigate the abuse of content commercialized via OTT platforms. It calls for greater awareness and enforcement of copyright laws in the evolving era of OTT, and the need for collaboration between OTT platforms, production companies, and other stakeholders to address the challenges of copyright infringement in cyberspace.
Keywords: Infringement; Evolving; Content Piracy